Effectiveness of viterna addition to feed on survival and growth rate of freshwater pomfret (Colossoma macropomum) - Antoni, Antoni; Febri, Suri Purnama; Komariyah, Siti; Haser, Teuku Fadlon; Sari, Herlina Putri Endah; Rusydi, Rachmawati; Akmal, Yusrizal (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2024)
Pomfret (Colossoma macropomum) is one of the freshwater fish commodities that is widely cultivated and widely consumed by Indonesian people. This research aims to determine the effectiveness of doses of viterna addition on feed to the survival and growth rate of pomfret. The method used in this study was an experimental method with four treatments and repeated three times. Viterna doses were PI: 0 ml (control), P2: 10 ml, P3: 15 ml and P4: 20 ml. The result showed that there was a significant effect on absolute length growth, absolute weight growth, and daily growth rate. While the survival and feed conversion rate did not have a significant effect. The highest absolute length growth result was P4=3.82 cm, while the lowest absolute length growth result was P1 3.01 cm. The highest absolute weight growth result was P4 9.88 g, while the lowest absolute weight growth was P1 6.40 g. The highest daily growth rate was P4 2.35%, while the lowest daily growth rate was P1 1.77%. From the results of adding viterna with different doses to the feed, the higher the dose of viterna given, the resulting growth has a better category.